ANALISIS FAKTOR – FAKTOR YANG MEMPENGARUHI NILAI EKSPOR INDUSTRI KREATIF BIDANG KERAJINAN KAYU DI INDONESIA - Wijaya, I Nyoman Suprapta; Purwanti, Putu Ayu Pramitha (E-Jurnal Ekonomi Pembangunan Universitas Udayana, 2021)
International trade in the current era of globalization has major influence on economic development in the world, requires the Indonesian state develop its industrial sector. The handicraft industry is one potential industries in Indonesia. The objectives of this study are (1) analyze effect of United States dollar exchange rate, inflation and production quantity simultaneously on the export value of the creative woodcraft industry in Indonesia, and (2) analyze effect of United States dollar exchange rate, inflation and production quantity partially on the the export value of the creative wood handicraft industry in Indonesia. The data used are secondary data with multiple linear regression analysis techniques. The results show that the US dollar exchange rate, inflation and production quantity simultaneously affect the export value of wood crafts in Indonesia. The US dollar exchange rate partially has a positive and significant effect on the export value of wooden handicrafts in Indonesia. Inflation partially has a negative and insignificant effect on the export value of wood handicrafts in Indonesia. Production quantity partially has a positive and significant effect on the export value of wood handicrafts in Indonesia. Key words: United States dollar exchange rate, inflation and production quantity of wood handicraft export value